Avaliação do torque dos braquetes de incisivos da prescrição MBT - Bóbbo, Maira Ferreira (2006)
The main goal of this research was to compare torque values of MBT brackets of Upper Central and Lateral Incisors and Lower Incisors with values prescribed by technical authors. The following brands, commercially available in the Brazilian market were selected: Abzil, American Orthodontics, Morelli, Ortho Organizers, TP Orthodontics and 3M Unitek (20 brackets each brands). The methodology used was to position the brackets in a standard mold and observe them through a Carl Zeiss microscope, evaluating the images using software, which allowed the determination on reference points, force lines on brackets and finally the torque measurement. The results demonstrated that the Morelli brand Upper Central Incisors demonstrated a statistically significant difference between the study measurement and the MBT values. The Upper Lateral Incisors of American Orthodontics, Morelli and TP Orthodontics are statistically significantly different than the standard. The Llower Incisors of American Orthodontics, Ortho Organizers e 3M Unitek also demonstrated a statistically significant difference. Comparing the torque average and standard deviation of the commercial brands above mentioned we concluded that, regarding the Upper Central Incisors the brand Morelli presented average with statistically significant difference than the other brands, least Abzil. For the Upper Lateral Incisors, the brackets of American Orthodontics demonstrated statistically significant difference when compared to the brands Abzil, Ortho Organizers and 3M Unitek and the brand Morelli presented average with statistically significant difference than other brands. The Abzil Lower Incisors demonstrated average with statistically significant difference when compared with American Orthodontics and 3M Unitek, and the brand American Orthodontics demonstrated statistically significant difference to TP Orthodontics.